EFFORTS TO IMPROVE INDONESIAN LANGUAGE LEARNING OUTCOMES OF LETTER RECOGNITION MATERIALS THROUGH THE DISCOVERY LEARNING MODEL IN GRADE I STUDENTS OF SD N 1 A.WIDODO - Anjani Malika dewi (Teaching and General Education Studies, 2025)
This research aims to determine the completeness of Indonesian language learning outcomes. Increasing Indonesian language learning outcomes. Material for recognizing letters through the discovery learning model in class I students at SD N 1 A. The type of research is Classroom Action Research (PTK) with 16 class I students as subjects, consisting of 9 men and 7 women. Data was collected through tests, observation and documentation, and analyzed descriptively qualitatively and descriptively quantitatively. This research consists of three cycles with planning, implementation, observation and reflection stages. The results show that Indonesian language learning outcomes have increased. In conclusion, Indonesian Language Learning Outcomes. Efforts to Improve Indonesian Language Learning Outcomes for Recognizing Letters Material through the Discovery Learning Model have increased and are an effective alternative for improving student learning outcomes.